2021
DOI: 10.3390/horticulturae7100354
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Organic, Inorganic Fertilizers and Their Combinations on Fruit Quality Parameters in Strawberry

Abstract: Strawberry (Fragaria × ananassa Duch.) is widely grown and highly appreciated by consumers around the world for its delicious, soft, and highly nutritious fruits. Turkey is one of the most important strawberry producers in the world. Strawberry cultivation in Turkey typically involves the use of chemical fertilizers and more recently organic and organic+ chemical fertilizers have been started to use in commercial production to produce healthier fruits. Therefore, in this study, we investigated the effect of or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 59 publications
5
15
1
Order By: Relevance
“…There are many reports on the superiority of ORG-produced fruits and vegetables over conventional cultivation practice regarding ascorbic acid concentration [2,6,7,32]; however, Asami et al [7] pointed out the superiority of sustainable (similar to INT management practiced here) over conventional management, which supports the present findings. Furthermore, results similar to ours have been reported by others [26,40], although working with ORG and conventionally produced strawberries, whereas [20,29] found a lower concentration of ascorbic acid in ORG-produced strawberries, obscuring, even more, the effects of cultivation management on its concentration in the fruit.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…There are many reports on the superiority of ORG-produced fruits and vegetables over conventional cultivation practice regarding ascorbic acid concentration [2,6,7,32]; however, Asami et al [7] pointed out the superiority of sustainable (similar to INT management practiced here) over conventional management, which supports the present findings. Furthermore, results similar to ours have been reported by others [26,40], although working with ORG and conventionally produced strawberries, whereas [20,29] found a lower concentration of ascorbic acid in ORG-produced strawberries, obscuring, even more, the effects of cultivation management on its concentration in the fruit.…”
Section: Discussionsupporting
confidence: 90%
“…Carbohydrates, as well as the sweetness index of the ORG-cultivated fruits, were found to be, in most cases, higher those of I-AGR-cultivated fruits and similar to those determined under I-ACT practice. According to [29], the combination of chemical fertilizers plus organic matter in three strawberry cultivars led to a similar concentration of sugars to those measured under ORG fertilization, with similar conclusions reported by others [10,15,18,28].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Earlier, Kilic at el. [34] reported that the organic acid content is higher in organic compared to inorganic fertilizer treatments. In addition, the T1 treatment resulted in faster fruit ripening than the T2 treatment, thus resulting in a significantly higher organic acid content in the fruit pulp.…”
Section: Sugar and Organic Acidmentioning
confidence: 99%
“…Strawberry fruit is rich in bioactive compounds such as phenolic acids, flavonoids, sugars, organic acids, and anthocyanins [ 2 ]. Strawberry fruit, which is rich in biochemical compounds, is preferred by people who want a healthy diet [ 3 ]. Strawberry fruit is widely grown in many countries today and is preferred both for fresh consumption and as a functional product in many fields, especially in the food industry.…”
Section: Introductionmentioning
confidence: 99%